International regionalism and national constitutions : a jurimetric assessment - de Lombaerde, Philippe (2014)
Considers a large global sample of constitutional texts and assesses to what extent and how they refer to the increasingly important phenomenon of international regionalism or regional integration and how they deal with potential sources of tension and contradictions between the national legal systems and the emerging regional regulatory universes.